Opportunities and challenges in developing a whole-of-government national food and nutrition policy: lessons from Australia’s National Food Plan - Carey, Rachel; Caraher, Martin; Lawrence, Mark; Friel, Sharon (Public health nutrition, 2016)
The present article tracks the development of the Australian National Food Plan as a 'whole of government' food policy that aimed to integrate elements of nutrition and sustainability alongside economic objectives. The article uses policy analysis to explore the processes of consultation and stakeholder involvement in the development of the National Food Plan, focusing on actors from the sectors of industry, civil society and government. Existing documentation and submissions to the Plan were used as data sources. Models of health policy analysis and policy streams were employed to analyse policy development processes. Australia. Australian food policy stakeholders. The development of the Plan was influenced by powerful industry groups and stakeholder engagement by the lead ministry favoured the involvement of actors representing the food and agriculture industries. Public health nutrition and civil society relied on traditional methods of policy influence, and the public health nutrition movement failed to develop a unified cross-sector alliance, while the private sector engaged in different ways and presented a united front. The National Food Plan failed to deliver an integrated food policy for Australia. Nutrition and sustainability were effectively sidelined due to the focus on global food production and positioning Australia as a food 'superpower' that could take advantage of the anticipated 'dining boom' as incomes rose in the Asia-Pacific region. New forms of industry influence are emerging in the food policy arena and public health nutrition will need to adopt new approaches to influencing public policy.